Pendidikan Karakter sebagai Fondasi Pencegahan Anak Berurusan Hukum: Pendekatan Edukatif dan Preventif - Us’an, Us’an; Alfasyah, Dandy Yusuf; Akhmad, Fandi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The phenomenon of children in conflict with the law (ABH) indicates a fundamental problem in the process of character formation from an early age. Character education is seen as the most strategic foundation in preventing deviant behavior in children that could potentially lead to legal problems. This study aims to analyze the role of character education as an educational and preventive approach to prevent children from having problems with the law. The method used is a literature study by analyzing various scientific sources in the form of books, journal articles, and previous research results relevant to the topic of character education and preventing children from having problems with the law. The results of the study indicate that character education integrated with the family and school environment, such as positive habits, continuous guidance, cooperation, affection, and role models, plays an effective preventive instrument in minimizing the risk of children getting involved in legal problems. Thus, strengthening character education systematically and continuously is something that urgently needs to be done within the framework of child protection and the development of human resources with character.